Total White blood count, absolute neutrophil count and neutrophil lymphocyte ratio and heart failure in patients with STEMI - Ahmed Raza Khan, Naseem Akhter, Ali Sarfraz, Shazia Maqbool, Maliha Asif, Asma Ejaz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In Pakistan risk factors for coronary Artery disease are highly prevalent. The cause of 30-40% death in Pakistan is coronary artery disease. Inflammatory markers have a significant role in cardiovascular events: These markers are C - reactive protein, interlukin-6 and high erythrocyte sedimentation rate. Few parameters are proposed to pedicel the outcome in coronary artery disease that includes WBC count neutrophil count and neutrophil/lymphocyte ratio. Methodology: It was a prospective descriptive study conducted in the Cardiac unit, Ibn-e-Siena Hospital, Multan. Data of 159 patients who met the inclusion criteria was collected. Patient’s demographic details were noted. All patients having any of these, cardiogenic shock, pump failure (ejection ≤30%) and acute pulmonary edema were taken as having heart failure. Results: In this study main population was from age group 61-70 and 51-60 years age group. White blood count, absolute neutrophil count and neutrophil lymphocyte ratio was compared in patients with heart failure and without heart failure and significant difference was noted among groups. Conclusion: So white blood cell count, absolute neutrophil count and neutrophil lymphocyte ratio are good predictor of heart failure in patients with STEMI. So these parameters can be used to stratify high risk patients and can help in early identification and management of high risk patients Keywords: heart failure, neutrophil lymphocyte ratio, white cell count, ST segment elevation myocardial infarction.